CHAPTER 4 High Temperature Oxidation of Stainless Steels - Somrerk Chandra-ambhorn; Shigenari Hayashi; Laurence Latu-Romain; Patthranit Wongpromrat (My University, 2020)
This chapter is dedicated to the description of high temperature oxidation of both chromia and alumina forming alloys. The defect structures of iron and chromium are firstly reviewed. The effects of elements on stainless steel oxidation behaviour are further addressed. For the chromia-forming stainless steel, the oxidation rate is reduced with the increased silicon content but not in a monotonic manner. Titanium and niobium can reduce breakaway oxidation of Fe–18Cr–10Ni austenitic stainless steel. Titanium can enhance the adhesion of scale to the Fe–18Cr by mechanical keying effect of TiO 2 formed at the steel/scale interface. For the alumina-forming stainless steel, the formation of alumina and its transformation during oxidation are reviewed. Chromium can be added to reduce the critical aluminium content in the steels in order to form alumina at high temperatures. The addition of reactive elements with appropriate level can improve scale adhesion and reduce the steel oxidation rate. Refractory element like molybdenum can increase strength of material but also accelerate the oxidation rate of the steels containing reactive elements. The development of new alumina-forming austenitic alloy grades is finally described.
Keywords: Chromia; High-Temperature Coating Behaviors